Implementation Of Pedagogical Technologies In Primary Classes - Bobomurodov Kupaysin Abduvayitovich (Genius Publishing Group, 2024)
In this article, the application of pedagogical technologies in the educational process is considered one of the most urgent tasks today and is covered in a very broad sense. Today, teaching based on pedagogical technologies in the primary education process is considered the demand of the era
Keywords: Educational system; medical laws; technological